Chiral separation by simulated moving bed chromatography: comparison between configurations using a low number of columns - Pais, Luís S. (2010)
Recent applications in the pharmaceutical industry use SMB systems containing a low total number of columns, usually four to eight. The objective of this work is to evaluate and compare the performance of SMB systems with a low number of columns. Simulation results will be shown for SMB units with 4, 5, and 6 columns. Also the two strategies of modeling, TMB and SMB, will be compared for these configurations.